THE INFLUENCE OF HEALTH EDUCATION WITH BOOKLET MEDIA AND DEMONSTRATION ON PREGNANT WOMEN'S KNOWLEDGE OF ANEMIA PREVENTION - Satiyem Satiyem; Luthfianingrum Nur Azizah; Istikhomah Istikhomah (Universitas Kusuma Husada Surakarta, 2025)
Background: Pregnant women in Indonesia often experience anaemia. Health education about anaemia and its prevention is essential for increasing the awareness of pregnant women, which helps improve the health of both the mother and the fetus. This study aims to determine the influence of health education about anaemia using booklets and demonstrations on the knowledge of pregnant women in Serenan Village, Juwiring DistrictMethods: Pre-experimental research was used in this study. This study used the one-group pretest-posttest method. Total sampling was used to select 22 pregnant women from Serenan Village, Juwiring District. This study used questionnaires and booklets. This research uses the Wilcoxon test.Results: Based on univariate analysis, 19 respondents or 86.4% of the sample, were aged between 20 and 35 years. A total of 16 respondents, or 72.7% were primiparas based on parity. The majority of respondents, 16 (72.7%), had completed high school. Regarding the understanding of pregnant women before receiving health education, 14 respondents (63.6%) had sufficient knowledge, eight respondents (36.4%) had inadequate information, and none had good knowledge. After their health education, 20 respondents (90.9%) reported having high knowledge, 2 (9.1%) reported having sufficient understanding, and none reported having poor knowledge. There was an effect of health education using booklets and demonstrations on pregnant women's knowledge about anaemia prevention, with a p-value of 0.000. Conclusion: The implication of this study is that the combination of booklets and demonstrations can be a good method for increasing pregnant women's knowledge.